Predlog nadgraditve programa vzgoje za zdravje za otroke in mladostnike na podlagi ocene obstoječega stanja organizacije in izvajanja programa v Sloveniji - Magajna, Anja (Javno zdravje, 2022)
Health education is a lifelong learning process that starts in childhood and aims to build individuals' resources through pedagogical and motivational approaches, and to strengthen skills and awareness of improving their own health. In this paper, we focus on the organization and implementation of a formally defined health education program for children and adolescents in primary schools in Slovenia, with the aim of summarizing the current state of the organization of the program and suggesting improvements.
Keywords: children and adolescents; health education; nadgradnja; organizacija in implementacija; organization and implementation; otroci in mladostniki; upgrades; vzgoja za zdravje